Obinutuzumab does not improve complete methabolic response but does not compromise mobilization or engraftment of autologous peripheral blood stem cells in diffuse large B cell lymphoma: Results from a fondazione italiana linfomi prospective phase II study (the GIOTTO study). Issue 4 (5th June 2022) - Rigacci, Luigi; Battistini, Roberta; Kovalchuk, Sofia; Zoli, Valerio; Puccini, Benedetta; Evangelista, Andrea; Arcaini, Luca; Flenghi, Leonardo; Visco, Carlo; Mian, Michael; Di Rocco, Alice; Peracchio, Claudia; et al.
Abstract: Salvage immunochemotherapy and transplant consolidation is the standard treatment for relapsed or refractory (R/R) diffuse large B‐cell lymphoma (DLBCL). We tested a combination of Obinutuzumab and DHAP for treating R/R DLBCL. The primary end point was the rate of complete metabolic response (CMR). Secondary end points were stem cell mobilization, stem cell engraftment, overall survival, and feasibility. In this prospective, phase‐2, single‐arm trial (EudraCT 2014‐004014‐17) patients received the standard three doses of Obinutuzumab for the first cycle, and then one dose. Patients with CMR were consolidated with an autologous stem cell transplantation (ASCT). An interim analysis was provided after the first 29 patients to confirm the initial null hypothesis that at least 10/29 patients would achieve CMR. Among the 29 patients evaluated for the first stage only six patients (6/29, 21%) achieved CMR, thus, study enrollment was stopped. Nine patients exhibited extra‐hematologic toxicities ≥ grade 3. Among the 19 patients that started stem cell mobilization, one failed (5%) and 18 achieved mobilization (95%). Of these 18 patients, nine were reinfused. Mobilization was observed in 16 patients (89%) after one or two apheresis rounds. The mean number of CD34 + cells mobilized was 5.8 × 10 6 /Kg (median: 5.5, IQR: 5–6.75). The mean number of reinfused CD34 + cells in the nine patients was 4.1 × 10 6 /Kg (median: 4.1, IQR: 3.5–5). Obinutuzumab combined with DHAP did not compromise stem cell mobilization or engraftment after ASCT in patients with DLBCL. However, Obinutuzumab + DHAP provided a lower CMR rate than expected.